2014
DOI: 10.1021/jp503702t
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Thermochemistry Associated with the Carbon–Carbon Coupling Reactions of Furan and Furfural Using ab Initio Methods

Abstract: Upgrading furan and small oxygenates obtained from the decomposition of cellulosic materials via formation of carbon-carbon bonds is critical to effective conversion of biomass to liquid transportation fuels. Simulation-driven molecular level understanding of carbon-carbon bond formation is required to design efficient catalysts and processes. Accurate quantum chemical methods are utilized here to predict the reaction energetics for conversion of furan (C4H4O) to C5-C8 ethers and the transformation of furfural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…In the Diels−Alder pathway ((reactants → intermediates (FF-1 → FF-9) → products), shown in Figure 5a, the cycloaddition reaction between two furans (FF-1 → FF-2) requires a barrier of 0.78 eV (FF-1-TS) to form the Diels− Alder adduct (4,7-dihydro-4,7-epoxybenzofuran, FF-2). From our previous studies, the barrier required for the Diels−Alder reaction of two furan molecules is 1.24 eV, 28 indicating a reduction of the barrier by 0.46 eV in the presence of HZSM-5 for the furan coupling reaction. Upon the formation of Diels− Alder product (FF-2), a proton of HZSM-5 is transferred to the adduct (see FF-2 → FF-3), followed by a C−OH bond cleavage and proton transfer (see FF-4 → FF-5) back to the zeolite to form benzofuran-4-ol (FF-5).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…In the Diels−Alder pathway ((reactants → intermediates (FF-1 → FF-9) → products), shown in Figure 5a, the cycloaddition reaction between two furans (FF-1 → FF-2) requires a barrier of 0.78 eV (FF-1-TS) to form the Diels− Alder adduct (4,7-dihydro-4,7-epoxybenzofuran, FF-2). From our previous studies, the barrier required for the Diels−Alder reaction of two furan molecules is 1.24 eV, 28 indicating a reduction of the barrier by 0.46 eV in the presence of HZSM-5 for the furan coupling reaction. Upon the formation of Diels− Alder product (FF-2), a proton of HZSM-5 is transferred to the adduct (see FF-2 → FF-3), followed by a C−OH bond cleavage and proton transfer (see FF-4 → FF-5) back to the zeolite to form benzofuran-4-ol (FF-5).…”
Section: Resultsmentioning
confidence: 92%
“…In addition to methanol related reactions, investigations have been also carried out on other oxygenated species. Recently, furans derived from biomass have received increasing attention in catalytic biomass conversion to fuels. ,,,, Huber and co-workers have reported that furan forms aromatics and olefins in HZSM-5, in which benzofuran, as the major furan coupling product (see Figure ), is an important intermediate for the formation of benzene and alkenes. , In addition, Williams et al have reported a “green” route to convert 2,5-dimethylfuran (DMF) and ethylene to p -xylene in HY zeolite with a 75% selectivity at 300 °C. The reaction occurs via Diels–Alder reaction followed by dehydration reaction .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chemical composition of biodiesel is an inherent mixture of methyl esters of long, unsaturated fatty acids, such as oleic acid or linolenic acid, typically contain 16–18 carbon atoms with one to three CC double bonds in the hydrocarbon chain. A complete study of the intrinsic thermodynamic parameters controlling the different bond strengths is a crucial factor in the search of more efficient biofuels. …”
Section: Introductionmentioning
confidence: 99%